PERAN PENTING PENGENDALIAN INTERNAL DALAM SISTEM INFORMASI AKUNTANSI - Khusnul Fu'ad (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2015)
The current business environment changes rapidly. The company must have a reliable internal control system in order to survive and highly competitiveness. This paper discusses about the important role of internal control in Accounting Information Systems. The study of literature is used in this paper. The author presents five old papers as an object of  it.The author finds six important role of Internal Control System. The first is giving a great influenced on Accounting Information Systems which is computer-based, Internal Control Systems can prevent excessive resources within the company, Creating accountability of the financial reports, increasing the credibility and quality to the company, the management becomes easy to make the decision, and preventing the fraud. Accounting Information Systems which is computer based can’t do well without controlling from the management Keywords:Accounting Information System, Internal Control, The Important Role